Visualisation of stereotactic radiolesions by nuclear magnetic resonance. Issue 1 (January 1985) - Leksell, L; Herner, T; Leksell, D; Persson, B; Lindquist, C
Abstract : The ability to visualise stereotactic brain lesions produced by irradiation from the stereotactic Gamma Unit at the Karolinska Hospital was investigated. A patient who had undergone bilateral stereotactic gamma capsulotomy in two stages was examined by the nuclear magnetic resonance imaging technique, which demonstrated that the stereotactic lesions in the internal capsule could be visualised in the immediate postoperative period. This gives stereotactic radiosurgery a reliable anatomical basis and facilitates the planning and follow-up studies in this type of cerebral surgery.